The Connection of Play Activity and the Understanding of Emotions in Older Preschoolers - I.A. Ryabkova; J.I. Timokhina; E.Yu. Myastkovskaya (Психолого-педагогические исследования)
Play is traditionally associated with the emotions of a child, however, the results of research in this area are ambiguous. Available works are mainly concentrated in foreign sources since this topic is practically not studied in Russia. The purpose of this study is to fill this gap – to study the relationship between the play activities of preschoolers and their understanding of emotions. The hypothesis is that there is a direct connection between the level of development of pretend play for children 5-7 years old and their emotional development. To test the hypothesis, a modified method for evaluating play activity of L.B. Baryaeva and A.P. Zarin, as well as the Test for understanding emotions, were used. Play was evaluated twice, with a difference of 2 weeks, average scores were displayed. Emotion comprehension testing was carried out using the specially developed ChildStudy MSU computer program. The study was conducted in five kindergartens working under general education programs. The sample consisted of 50 children (21 girls, 42%), the age of the subjects ranged from 5 years 0 months to 7 years 5 months. As a result of the study, no correlations were found between scores on play activity and the understanding of emotions. Another noteworthy significant result is that children who correctly solve tasks for understanding mixed emotions have more complex creative play.